2007
DOI: 10.1039/b704491g
|View full text |Cite
|
Sign up to set email alerts
|

Autoionization at the surface of neat water: is the top layer pH neutral, basic, or acidic?

Abstract: Autoionization of water which gives rise to its pH is one of the key properties of aqueous systems. Surfaces of water and aqueous electrolyte solutions are traditionally viewed as devoid of inorganic ions; however, recent molecular simulations and spectroscopic experiments show the presence of certain ions including hydronium in the topmost layer. This raises the question of what is the pH (defined using proton concentration in the topmost layer) of the surface of neat water. Microscopic simulations and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
191
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(206 citation statements)
references
References 80 publications
15
191
0
Order By: Relevance
“…In the bulk, both ionic defects can diffuse rather rapidly, on a timescale of 10-100 femtoseconds, consistent with previous reports in the literature (29). However, on segregating to the surface, we find that the mobility of both species is reduced by orders of magnitude.…”
Section: Resultssupporting
confidence: 81%
“…In the bulk, both ionic defects can diffuse rather rapidly, on a timescale of 10-100 femtoseconds, consistent with previous reports in the literature (29). However, on segregating to the surface, we find that the mobility of both species is reduced by orders of magnitude.…”
Section: Resultssupporting
confidence: 81%
“…Some experimental (9) and theoretical (7,25,26) results were interpreted to signify that the air-water interface is more acidic than bulk water, whereas others reached the opposite conclusion (8,11,21,23,27). The impasse stems in part from the failure to recognize that acidity is a relative concept describing the extent of proton sharing between two conjugate acid/base pairs under specified conditions.…”
mentioning
confidence: 99%
“…At neutral pH, there is the experimental zeta potential evidence for a lower concentration of hydrogen ions than hydroxide ions at the surface. Vácha et al (2008b) has suggested that techniques scrutinizing the water-gas interface from the vapor side can see it as acidic, while those examining it from the aqueous bulk side it will appear as basic. However, there seems little evidence in support as no experimental method has unambiguously shown that the surface is positive but several show it unambiguously as being negative (Hänni-Ciunel et al 2009;Beattie et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although early Monte Carlo studies on isolated clusters indicated that the hydroxonium ion prefers the interior of the clusters (Svanberg and Pettersson, 1998), later studies, including density functional analysis, suggest that they prefer the exterior of the cluster Vácha et al 2007). Note however that such clusters contain mainly surface molecules, are charged particles and not neutral and are acidic with a pH equivalent to less than zero; with hydrogen ion concentration at least three orders of magnitude higher than those present at the lowest isoelectric points proposed.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation